An Emerging New Paradigm in Opioid Withdrawal: A Critical Role for Glia-Neuron Signaling in the Periaqueductal Gray. (2nd August 2012) - Ouyang, Handong; Liu, Shue; Zeng, Weian; Levitt, Roy C.; Candiotti, Keith A.; Hao, Shuanglin
Abstract : The chronic use of opiates (i.e., narcotics such as the natural derivatives of opium including morphine or codeine) or opioids (i.e., semisynthetic derivatives of opium and other molecules that activate opioid receptors) induces dependence, which is associated with various specific behavioral and somatic signs after their withdrawal or after the administration of an opioid antagonist. Among the brain regions implicated in opiate dependence and withdrawal, the periaqueductal gray area (PAG) appears to be critical in regulating the complex signs and symptoms of opioid withdrawal. Numerous neurochemical mechanisms in the PAG have been identified that may contribute to the opioid withdrawal syndrome. Accumulating evidence suggests that glial activation leading to the release of proinflammatory molecules acting on neurons is important in the complex syndrome of opioid dependence and withdrawal. This paper focuses on the recent advances in our understanding of the vital role that glia-neuron interactions play in opioid dependence and withdrawal within the PAG. We summarize those neurochemical mechanisms associated with opioid withdrawal including the recently defined importance of TNF α release from activated glial cells that communicate with TNF receptors on PAG neurons.